Collaborative Governance In The Development Of Kalimas Boat Ride Tour In Surabaya City - Rosanjaya, Loktavia; Wahyudi, Kalvin Edo (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
Collaboration is the main key in tourism development, including in Surabaya City which has the potential for water tourism, such as Kalimas Boat Ride Tour. This tourist destination offers a unique experience with a route through various tourist attraction spots and historical buildings. However, the development of this destination requires the support of various parties so that Surabaya City Government seeks synergy with stakeholders to encourage collaboration. Thus, collaborative governance emerges as a relevant order to strengthen the development of Kalimas Boat Ride Tour in this research. The purpose of this research is to describe the collaborative governance process in the development of Kalimas Boat Ride Tour in Surabaya City. This research uses descriptive research methods with a qualitative approach. Data collection techniques, namely observation, document collection, and interviews. Test validity by means of triangulation techniques. The results of this study show three research focuses which have varied results, namely: 1) Collaborative dynamics there are shortcomings in terms of trust and limitations on budget resources and facilities 2) Collaborative actions carried out by organising events with the community have gone well 3) Impacts and adaptation obtained have appeared and felt the positive influence of each actor involved.